The reservoir as an asset proceedings of the ninth conference of the British Dam Society held at the University of York, 11-14 September 1996. (Thomas Telford, 1996)
A collection of papers on a range of subjects' in the field of dam engineering, including embankment dams, concrete dams service reservoirs, investigations and reservoir safety standards. The operation of the Reservoirs Act 1975 from an owner's and a Supervising Engineer's view is also discussed.